Efektivitas Ensiklopedia sebagai Suplemen Bahan Ajar Digital pada Muatan PPKn Materi Keberagaman Budaya Bangsa Indonesia Kelas V SD Negeri 18 Pontianak Utara - Sari, Nanda Permata; Kresnadi, Hery; Hamdani, Hamdani (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
This research aims to determine the effectiveness of an encyclopedia to make students more interested, enthusiastic, less prone to boredom, and facilitate their understanding of the material presented through this instructional material. The study employs a descriptive research design with a qualitative approach. The participants in this study are all fifth-grade students of class V B, totaling 33 individuals. Qualitative data are obtained from interviews conducted by the researcher with selected students based on predefined categories. The validity of the instructional material design has been validated by media and subject matter experts, receiving an excellent category for use but still requiring revision before being tested. The data collection techniques in this study include interviews and questionnaires. The data collection instrument used in this research is a test to measure students' abilities in the effectiveness of the encyclopedia as a supplementary digital instructional material. The results obtained in this study show that students' responses fall into the very positive category, indicating that it is highly suitable for use with audiovisual displays in the PPKn (Civics Education) learning content on the cultural diversity of the Indonesian nation. It received very positive responses from students, and the learning outcomes obtained by the students were good, as seen in the evaluation test results. The encyclopedia significantly helps students understand this material, and its flexible use further facilitates students' learning at home. Considering the responses and learning outcomes of the students, the effectiveness of the encyclopedia as a supplementary digital instructional material makes it easier for teachers and students to revisit the content of the cultural diversity of the Indonesian nation.